TELA’AH KONSEP NILAI-NILAI PENDIDIKAN ISLAM - Ali Mustofa (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
Islamic education is an operational basis for realizing the ideal basis for Islamic education sources. Therefore, planting the values of Islamic education is an absolute must. The values of Islamic education can be concluded that Islamic education aims to inform, transform and interlate Islamic values in the hope that it can raise awareness and develop aspects of a good and correct spiritual life in order to realize the whole Muslim person with the characteristics of faith, piety, and character. noble character, smart, skilled and responsible. The kinds of values of Islamic education are faith, worship values and moral values.